2018
DOI: 10.3390/catal8120600
|View full text |Cite
|
Sign up to set email alerts
|

BF3·Et2O-Promoted Decomposition of Cyclic α-Diazo-β-Hydroxy Ketones: Novel Insights into Mechanistic Aspects

Abstract: We report novel insights into the cascade rearrangement of destabilized vinyl cations deriving from the BF3·Et2O-induced decomposition of cyclic α-diazo-β-hydroxy ketones in turn prepared by aldol-type condensation of cycloalkanones with diazoacetone. Complexation of the hydroxy group of the α-diazo-β-hydroxy compound with the Lewis acid is the first event, followed by the generation of the cycloalkanylidenediazonium salt that, after nitrogen loss, produces the highly reactive vinyl cation. The subsequent ring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Although vinyl cations have been studied for over 60 years, a lack of methods to generate these highly reactive intermediates has hindered the development of general, synthetically useful reactions. , However, the recent realization of milder ways to form vinyl cations has led to renewed interest in their reactivity. For example, our group has taken advantage of vinyl cations to develop a ring fragmentation reaction, as well as methods to form cyclopentenones , and indenones (Scheme ). These reactions take advantage of Padwa and Pellicciari’s finding that vinyl cations are formed when β-hydroxy-α-diazo carbonyl compounds are treated with a Lewis acid .…”
Section: Introductionmentioning
confidence: 99%
“…Although vinyl cations have been studied for over 60 years, a lack of methods to generate these highly reactive intermediates has hindered the development of general, synthetically useful reactions. , However, the recent realization of milder ways to form vinyl cations has led to renewed interest in their reactivity. For example, our group has taken advantage of vinyl cations to develop a ring fragmentation reaction, as well as methods to form cyclopentenones , and indenones (Scheme ). These reactions take advantage of Padwa and Pellicciari’s finding that vinyl cations are formed when β-hydroxy-α-diazo carbonyl compounds are treated with a Lewis acid .…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the use of stoichiometric and catalytic reactions using boranes has shown a significant breakthrough in understanding their mode of activation. Although the reaction of diazo compounds with BF 3 •OEt 2 has been previously studied, 24,25 many new contributions to the field have emerged using triarylboranes, which is the focus of this review. In 2017, Stephan and co-workers reported that the Lewis acid-base adduct of Lewis acidic HB(C 6 F 5 ) 2 and B(C 6 F 5 ) 3 with the diazo compound diphenydiazomethane (Ph 2 CN 2 ) was important in its activation.…”
Section: Diazo Activation Using Stoichiometric Boranesmentioning
confidence: 99%